THE EFFECTS OF EXCESS PRECIPITATION FALLEN IN THE CURVATURE SUBCARPATHIANS (ROMANIA) DURING THE WARM PERIOD OF THE YEAR. CASE-STUDY: SĂRĂŢEL AND BĂLĂNEASA DRAINAGE BASINS - ANDUŢA GROFU; CARMEN-SOFIA DRAGOTĂ (Revue Roumaine de Géographie)
The present work aims at presenting the main characteristics of the pluviometric regime in the Bălăneasa and Sărăţel basins, represented by the quantitative parameters of the warm season (spring-autumn). The climatic data provided by the Pătârlagele Weather Station are representative for the geographical area we are interested in. The period analysed (1961–2007) is statistically relevant in terms of climatology, covering the standard climatological period (1961–1990), the last decade of the twentieth century and the early years of the current decade which are characterized by major extreme pluvial events on a global, regional and local scale. The distribution of precipitation quantities presents value differences on various time-scales. In the annual rain regime specific to the temperate-continental climate of Romania, the quantities of the warm semester have the greatest share. For adequate decisions to be made and implemented in order to diminish the negative environmental effects of excess/deficient precipitation, the present article has been aimed at establishing the multi-annual water values in the warm semester of the year. The analysis and conclusions are based on the annual, seasonal and monthly precipitation values, highlighting the value differences, imposed mainly by the complexity of the Subcarpathian Curvature sector.